Phenomenology of the Human Existence in Photography - Al-Sheikh, Hanan Muneer (International Journal of Psychosocial Rehabilitation, 2020)
Photography in the contemporary time considers a vital, important, rich, and meaningful element which certainly influenced the concept of artistic and philosophical photograph due to the rapid development in technology and communication methods which should be accompanied by the theoretical development that paves the way for the photographic concept and analyzes its various relationships.This study seeks to explore an important practical theoretical aspect, which called the phenomenological philosophy, whereas this modern, broad, and open philosophy is at the same time a coherent approach that can be implemented on the photograph and therefore it's possible to find a clear philosophical position concerned about photography. The photograph here isn't understood as only a configurable content, and the form can't be separated from the content in this context, but the analysis of the image depends on its full existence and continued presence launching from the things that were actually given, and depending on an intentional and conscious action to reach the truth that is represented in the art itself. Therefore, it's possible to say that implementation of the Phenomenological approach in the photography will make the existing and perceptual image or picture opens up continuously and overflows with the meaning as a result of meditation and perception.